Triclosan as a Genotoxic Compound for Drosophila melanogaster - Anitha, D; Shantha, SL; Krishnamurthy, V; Vanishree, R (Kathmandu University Journal of Science Engineering and Technology, 2008)
Triclosan [5, chloro-2-(2, 4-dichlorophenoxy) phenol] (CAS No. 3380-34-5) is extensively used as an antimicrobial agent in many pharmaceutical formulations. Understanding its genotoxic potential is the aim of this experimental study. Drosophila fulfils dual function in the field of genetic toxicology - firstly as an experimental organism for short term tests to identify carcinogens and secondly as a model for learning mechanistic pathways of mutagenesis induced by environmental toxicants. The mutagenesis in Drosophila melanogaster contributed by triclosan is the theme of this study. The Sex-linked recessive lethal (SLRL) test was conducted on stock of Drosophila melanogaster. Males of well-defined stock and appropriately marked balancer females of FM 7 stock with multiple inverted X-chromosomes were used for the experiment. The triclosan concentration was administered with exposure concentration ranging from 0.5 to 2 mg for adults. The results indicated significant reduction in the number of males in the F2 generation. The mortality of larval population was 100% suggesting the test required lowering of concentrations of triclosan that was administered particularly with respect to larvae. DOI: 10.3126/kuset.v4i1.2879 Kathmandu University Journal of Science, Engineering and Technology Vol.4, No.1, September 2008, pp 12-16